An extremely rare malignant tumour of nasopharynx: primary nasopharyngeal non salivary type adenocarcinoma - Sebastin, Emelda Rose; Darishini, Piriya; Ling, Tang Chian; Ser, Heng Pek (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Adenocarcinoma is commonly found in lung, prostate and gastrointestinal tract. Nasopharyngeal part contributes a very small percentage of adenocarcinoma as the most common histopathology found here is squamous cell carcinoma. We present a case of nasopharyngeal adenocarcinoma which is a very rare clinical presentation. This is 35 years old Iban gentleman, with underlying retroviral disease, hepatitis B on treatment, presented with right neck swelling for 3 months associated with right ear fullness. Examination showed unilateral right level II neck swelling and nasal endoscopy showed mass arising from right fossa of Rosen muller (FOR). The investigation done includes biopsy of right FOR and biopsy of right neck swelling with contrast enhanced computed tomography of neck, thorax and abdomen. The result of right FOR biopsy is non intestinal type adenocarcinoma, and biopsy of right neck swelling is reported as metastatic undifferentiated carcinoma. CECT NTAP showed asymmetry with fullness of right FOR associated with right level II cervical lymphadenopathy. Our centre managed this case with surgical intervention and patient underwent endoscopic nasopharyngectomy, and planned for right modified radical neck dissection (MRND). Patient defaulted our follow up after operation and was not keen for neck dissection surgery. He presented the second time with bilateral neck swelling and underwent chemotherapy and defaulted the follow up thereafter again. In conclusion the approach in treatment for nasopharyngeal carcinoma (NPC) and sino-nasal adenocarcinoma differs whereby the cornerstone management for the latter one is surgical intervention compared to the former which is radiotherapy. Hence early detection and treatment is essential.